Characterization of the CACNA1C-R518C Missense Mutation in the Pathobiology of Long-QT Syndrome Using Human Induced Pluripotent Stem Cell Cardiomyocytes Shows Action Potential Prolongation and L-Type Calcium Channel Perturbation. (August 2019) - Estes, Steven I.; Ye, Dan; Zhou, Wei; Dotzler, Steven M.; Tester, David J.; Bos, J. Martijn; Kim, C.S. John; Ackerman, Michael J.
Abstract : Background: The CACNA1C -encoded cardiac L-type calcium channel (Cav1.2) is essential for cardiocyte action potential duration (APD). We previously reported the CACNA1C-p.R518C variant associated with prolonged QT intervals, cardiomyopathy, and sudden cardiac death in several pedigrees. Methods: To characterize a patient-derived human induced pluripotent stem cell–derived cardiomyocyte (hiPSC-CM) CACNA1C-p.R518C model, CACNA1C-p.R518C hiPSC-CMs were generated from a 13-year-old man (QTc, >480 ms) with a family history of sudden cardiac death. An isogenic hiPSC-CM gene-corrected control was created using CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/clustered regularly interspaced short palindromic repeat–associated 9). APD and calcium handling were assessed by live cell imaging with Arclight voltage and Fluo-4 calcium indicators, respectively. The APD and L-type calcium channel biophysical properties were further assessed by whole-cell patch clamp technique. Results: The Bazett formula-corrected, Arclight-measured APD90 of CACNA1C-p.R518C hiPSC-CMs was significantly longer (622±11 ms; n=92) than the isogenic control hiPSC-CMs (453±5 ms; n=62; P <0.0001). Patch clamp assessment of CACNA1C-p.R518C hiPSC-CMs paced at 1 Hz confirmed a prolonged APD90 (689±29 ms; n=10) compared with the patient's isogenic control hiPSC-CMs (434±30 ms; n=8; P <0.05). Fluo-4–measured calcium transient decay time suggested calcium mishandling in CACNA1C-p.R518C. Patch clamp analysis revealed increased L-type calcium channel window current, slow decay time at various voltages, and increased late calcium current for CACNA1C-p.R518C hiPSC-CMs when compared with isogenic control hiPSC-CMs. Conclusions: Using patient-specific hiPSC-CM mutant and isogenic control lines, we demonstrate that the CACNA1C-p.R518C variant is the self-sufficient, monogenetic substrate for the patient's long-QT syndrome phenotype. These data further bolster the conclusion that CACNA1C is a bona fide, definite evidence long-QT syndrome susceptibility gene. Abstract : Supplemental Digital Content is available in the text.